MODERASI BERAGAMA DI KOMUNITAS GUSDURIAN PURWOKERTO - Gading Adi Danu Wijaya, Wijaya (Fakultas Ushuludin Adab dan Humaniora Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri, 2024)
This research discusses Religious Moderation in the Gusdurian Purwokerto community. The Gusdurian Community is a community that prioritizes the values of tolerance between religious communities. In this community there are many activities that can enable us as religious people to respect each other, and also give us an understanding of other religions where we as living creatures are created into tribes and nations. This research aims for everyone to be able and able to respect each other's differences, and also to provide love of peace where in this era there is a lack of tolerance between religious communities. Speaking of moderation, moderation in the Gusdurian community will require a deep understanding of the values and principles held by that community, which often include pluralism, tolerance, equality and social justice. Several principles of moderation that can be applied in this context include, Dialogical Approach, namely an approach that encourages open and constructive dialogue between community members to understand differences of opinion and reach understanding, Strengthening Empathy where this approach invites community members to understand and respect other people's perspectives and develop empathy towards them, Emphasis on Social Justice namely: Ensuring that policies and actions within the community aim to promote social justice and inclusion for all members, Education and Awareness: Providing space for learning and reflection on relevant social, political and religious issues with Gusdurian principles.